Cluster Differences in Antibiotic Resistance, Biofilm Formation, Mobility, and Virulence of Clinical Enterobacter cloacae Complex - Liu, Shixing; Chen, Liqiong; Wang, Lingbo; Zhou, Beibei; Ye, Dandan; Zheng, Xiangkuo; Lin, Yishuai; Zeng, Weiliang; Zhou, Tieli; Ye, Jianzhong (Frontiers in Microbiology, 2022)
Due to the lack of research on the characteristics of different clusters of Enterobacter cloacae complex (ECC), this study aimed to characterize and explore the differences among species of the ECC. Analysis based on hsp60 showed that E. hormaechei was predominant in ECC. Interestingly, the antibiotic resistance rates of clusters were different, among which E. hormaechei subsp. steigerwaltii (cluster VIII) and E. cloacae Ⅸ (cluster Ⅸ) possessed high resistant rates to ciprofloxacin and levofloxacin, but cluster Ⅱ (E. kobei) had low resistant rates. Cluster Ⅱ exhibited a strong biofilm formation ability. Different motility and protease production ability were shown for distinct clusters. PCR analysis showed that clusters I, Ⅲ, Ⅵ, Ⅷ, and Ⅸ carried more virulence genes, while cluster Ⅱ had fewer. Clusters Ⅰ, Ⅷ, and Ⅸ with high pathogenicity were evaluated using the Galleria mellonella infection model. Thus, the characteristics of resistance, biofilm-forming ability, mobility, and virulence differed among the clusters. The strains were divided into 12 subgroups based on hsp60. The main clusters of ECC clinical strains were I, II, III, VI, VIII, and IX, among which IX, Ⅷ, and I were predominant with high resistance and pathogenicity, and cluster II (E. kobei) was a special taxon with a strong biofilm formation ability under nutrient deficiency, but was associated with low resistance, virulence, and pathogenicity. Hence, clinical classification methods to identify ECC subgroups are an urgent requirement to guide the treatment of clinical infections.